2019
DOI: 10.18524/2307-4663.2019.2(46).163699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Effect of Two Dysbiosis Models in Wistar Rats

Abstract: Aim. To compare the changes of intestinal microbial composition of two models of dysbiosis induced by ceftriaxone (Cf) or the mix of ampicillin (Amp) and metronidazole (Met). Methods. The object of the study was the changes of fecal and mucosa-associated microbiota of colon and small intestine of Wistar male rats (m=170-200g, n=19). Cf was injected once a day for 14 days at a dose of 300 mg/ kg i.m. The mix of Amp (75 mg/kg) and Met (50 mg/kg) was injected once a day for 3 days per os. Animals were removed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Earlier studies have shown that dysbiosis, occurs as a result of the use of antibiotics, has a long-term nature, is not capable of disappearing on its own, and requires treatment. [34][35][36] Since there are conditions in which the use of probiotics is not recommended, we assumed that in such cases it may be appropriate to use products with prebiotic and nutraceutical effects. Black cumin can have a double effect on both the microbiota and intestinal epitheliocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that dysbiosis, occurs as a result of the use of antibiotics, has a long-term nature, is not capable of disappearing on its own, and requires treatment. [34][35][36] Since there are conditions in which the use of probiotics is not recommended, we assumed that in such cases it may be appropriate to use products with prebiotic and nutraceutical effects. Black cumin can have a double effect on both the microbiota and intestinal epitheliocytes.…”
Section: Discussionmentioning
confidence: 99%